Using Extension Projects to Improve Software Engineering Education and Software Quality: The Experience of the “Ricardo de Almeida Falbo” Software Engineering Practices Laboratory - Barcellos, Monalessa P.; Souza, Vítor E. Silva; Costa, Patrícia Dockhorn; Aguiar, Camila Zacche de (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Software Quality (SQ) is a fundamental aspect of Software Engineering (SE) and is approached in different ways and disciplines in Computer Science undergraduate courses. Considering the nature of SQ, its learning should be based on practical experiences. Recently, the curriculum guidelines for undergraduate courses in Brazil were changed to require that 10% of the course workload be dedicated to extension activities. Extension plays a crucial role in students’ education, as it aims to provide benefits for society and contribute to a more comprehensive education, including social aspects in addition to technical ones. Considering this scenario, the “Ricardo de Almeida Falbo” Software Engineering Practices Laboratory (LabES) was set up at DI/UFES. It aims to apply SE methods, techniques, and practices to enable students to produce quality software, bringing their education closer to the needs of the various productive sectors and producing results for society. In this paper, we introduce LabES, explain how it works, present some of the produced artifacts and projects, and share lessons learned.